Elementary Preservice Mathematics Teachers Fraction Knowledge: An Integrative Review of Research - Cody J. Perry (Educational Considerations, 2023)
Elementary preservice teachers struggle with fractions and explaining them despite taking numerous mathematics courses. Therefore, they may have issues when they teach fractions and related concepts. Since fractions underlie many concepts like algebra, improving teachers’ fraction knowledge is imperative. This integrative review of research synthesized findings about teachers’ fractions knowledge to provide potential strategies educator preparation programs (EPPs) can use to improve fraction mastery. The literature shows teachers lacked conceptual knowledge, used incorrect strategies and too few representations, and misunderstood magnitude and manipulatives. However, number lines and teaching conceptually helped improve mastery of fractions. Resolving issues with fraction mastery may help future teachers meet their students’ needs better. Therefore, EPPs should assess new students’ fraction knowledge and implement conceptual instruction, number lines, etc. In addition, future research should include viewing which conceptual strategies are most effective and determining if methods used for K-12 students will also work for aspiring teachers.
Keywords: Fractions; rational numbers; elementary; preservice teachers; teacher education